2015
DOI: 10.1080/14786419.2014.999240
|View full text |Cite
|
Sign up to set email alerts
|

New fatty acid, aromatic ester and monoterpenic benzyl glucoside from the fruits ofWithania coagulansDunal

Abstract: The fruits of Withania coagulans Dunal (family: Solanaceae) are sweet, sedative, emetic, alterative and diuretic; used to treat asthma, biliousness, strangury, wounds, dyspepsia, flatulent colic, liver complaints and intestinal infections in the indigenous system of medicine. Phytochemical investigation of the methanolic extract of W. coagulans fruits led to the isolation of a new fatty acid, an aromatic ester and a monoterpenic benzyl glucoside characterised as n-octatriacont-17-enoic acid (3), geranilan-10-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The primary amino acids found in the plant are proline, tyrosine, valine, hydroxyproline, glycine, cysteine, asparagine, glutamic, and aspartic acids. The major fatty acids found include arachidonic acid, stearic acid, palmitic acid, linoleic acid, and oleic acid [22]. Similarly, research found 20 constituents in the essential oil of the fruit of W. coagulans is primarily composed of sesquiterpenes (54%) and esters (21.50%), which are the dominant compounds.…”
Section: Nutritional Profilementioning
confidence: 95%
“…The primary amino acids found in the plant are proline, tyrosine, valine, hydroxyproline, glycine, cysteine, asparagine, glutamic, and aspartic acids. The major fatty acids found include arachidonic acid, stearic acid, palmitic acid, linoleic acid, and oleic acid [22]. Similarly, research found 20 constituents in the essential oil of the fruit of W. coagulans is primarily composed of sesquiterpenes (54%) and esters (21.50%), which are the dominant compounds.…”
Section: Nutritional Profilementioning
confidence: 95%
“…Major fatty acids include arachidonic acid, stearic acid, palmitic acid, linoleic and oleic acids [3]. Furthermore, n-octatriacont-17-enoic acid, geranilan-10-olyl dihydrocinnamoate (aromatic ester), and geranilan-8-oic acid-10-olyl salicyloxy-2-O-β-D-glucofuranosyl-(6 →1 )-O-β-D-glucofuranosyl-6 -n-octadec-9 ,11 -dienoate(monoterpenic benzyl glucoside) in consort with two already identified fatty acids named as n-dotriacont-21-enoic acid and n-tetratriacontanoic acid were characterized in berries [19]. Similarly, research also detected twenty constituents in the essential oil of the W. coagulans fruit including sesquiterpenes (54%) and esters (21.50%) as dominant compounds followed by the presence of fatty acids (5.5%) such as nonanoic acid, hexanoic acid, methyl ester of hexadecanoic acid, methyl ester of nondecanoic acid, methyl esters of 8,11-octadecadienoic acid, methyl ester of 9-octadecenoic acid, and ethyl ester of linoleic acid, alkanes (9.11%), and the aldehydes (0.32%) in smaller percentage [20].…”
Section: Nutritional Profilementioning
confidence: 99%